Charge Distribution and Imperfect Amphipathicity Affect Pore Formation by Antimicrobial Peptides - Mihajlovic, Maja (2012)
Antimicrobial peptides often permeabilize biological membranes via a pore mechanism. Two pore types have been proposed: toroidal, where the pore is partly lined by lipid, and barrel-stave, where a cylindrical pore is completely lined by peptides. What drives the preference of antimicrobial peptides for a certain pore type is not yet fully understood. According to neutron scattering and oriented circular dichroism, melittin and MG-H2 induce toroidal pores whereas alamethicin forms barrel-stave pores. In previous work we found that indeed melittin seems to favor toroidal pores whereas alamethicin favors cylindrical pores. Here we designed mutants of these two peptides and the magainin analogue MG-H2, aimed to probe how the distribution of charges along the helix and its imperfectly amphipathic structure influence pore formation. Molecular dynamics (MD) simulations of the peptides in a pre-formed cylindrical pore have been performed. The duration of the simulations was 136 ns to 216 ns. We found that a melittin mutant with lysine 7 neutralized favors cylindrical pores whereas a MG-H2 mutant with lysines in the N-terminal half of these peptides neutralized and an alamethicin mutant with a positive charge at the position 7 form semitoroidal pores. These results suggest that charged residues within the N-terminal half are important for the toroidal pore formation. Toroidal pores produced by MG-H2 are more disordered than the melittin pores, likely because of the charged residues located in the middle of the MG-H2 helix (K11 and K14). Imperfect amphipathicity of melitin seems to play a role in its preference for toroidal pores since the substitutions of charged residues located within the nonpolar face by hydrophobic residues suppress evolution of a toroidal pore. The mutations change the position of lysine 7 near the N-terminus, relative to the lower leaflet headgroups. The MD simulations also show that the melittin P14A mutant forms a toroidal pore, but its configuration diverges from that of melittin and it is probably metastable.